miR-129-5p Inhibits Bone Formation Through TCF4 - Yin, Chong; Tian, Ye; Yu, Yang; Yang, Chaofei; Su, Peihong; Zhao, Yipu; Wang, Xue; Zhang, Kewen; Pei, Jiawei; Li, Dijie; Chen, Zhihao; Zhang, Yan; et al. (Frontiers in Cell and Developmental Biology, 2020)
Osteoporosis is a frequently-occurring bone disease in middle-aged and aged men and women. However, current therapies on this disease are still not ideal. miRNA is a class of endogenous non-protein-coding RNA with a length of 18-25 nucleotides. miRNA have been identified as important regulators for development, metabolism, carcinogenesis and bone formation. miR-129-5p has been reported as a regulator of cancer and neuroscience, while studies about its function on bone formation is still limited. In this study, we investigated the function and mechanism of miR-129-5p on osteoblast differentiation and bone formation. We have assessed the expression of miRNAs in bone mesenchymal stem cells (BMSCs) from aging and menopause osteoporosis C57BL6 mice. The expression of miR-129-5p was altered in all osteoporosis models. Besides, the expression of miR-129-5p was negatively correlated with osteoblastic differentiation markers in the femur tissues of C57BL/6 mice of different ages. We further demonstrated that over-expression of miR-129-5p inhibited osteoblast differentiation in MC3T3-E1 cell line as well as bone formation of C57BL/6 mice. On the other hand, down-regulation of miR-129-5p enhanced osteoblast differentiation and bone formation. We also found that miR-129-5p inhibited wnt/β-catenin pathway in osteoblast. The target gene of miR-129-5p have been forecasted and proved as Tcf4. We further found that plasmid containing Tcf4 3’UTR sequence enhanced osteoblast differentiation as well as wnt/β-catenin pathway in MC3T3-E1 cells. To further investigate the rescue effect of miR-129-5p inhibitor, we manufactured bioengineered novel recombinant miR-129-5p inhibitor through E. coli system, and then tested its function. The results showed that the novel recombinant miR-129-5p inhibitor promoted osteoblast differentiation, and greatly ameliorated menopause osteoporosis in C57BL6 mice. In conclusion, we have discovered miR-129-5p as an inhibitor of bone formation. miR-129-5p inhibited downstream transcription factors of wnt/β-catenin pathway through targeting Tcf4. Moreover, novel recombinant miR-129-5p inhibitor showed rescue effect on osteoporosis. This study has revealed a new mechanism of osteogenic differentiation and provided novel therapeutic strategies for treatment of skeletal disorders.